ANALISIS DAYA SAING EKSPOR MINYAK KELAPA SAWIT (CPO) SUMATERA UTARA DI INDONESIA - Faoeza Hafiz Saragih; Dwidjono Hadi Darwanto; Masyhuri Masyhuri (Department of Agricultural Socio-Economics Faculty of Agriculture Universitas Gadjah Mada, 2013)
This study aims to : (1) CPO export trends and projections in North Sumatera (2) CPO export competitiveness of North Sumatera in Indonesia (3) factors that affect CPO export in North Sumatera. This research based on the background tat CPO export volume in North Sumatera which is now well below Riau Province, where previously the province of North Sumatera is Indonesia’s largest palm oil exporter.The data used are secondary data to the time period of the years 1980-2010. Data collecting obtained from BPS, Ministry of Agriculture and KPB PTPN. The analyze used model equation of least square to see the trends and projections 10 year lstr; RCA and AR index used to see competitiveness and ordinary least square (OLS) model used to see the factors that affected CPO export of North Sumatra.The result of study show that: (1) North Sumatera CPO export trend for 1980-2010 was positive and projections export for ten years later increased with average growth 4.649 percent, (2) North Sumatera still competitive in Indonesian CPO exports based on the average value of the RCA index 13.24905 but with weak growths as indicated by the AR index of 0.232 caused by the potential land was small, production growth was slowly, the low productivity and the transfer of export port by exporters, (3) North Sumatra CPO exports affected positively by Doller exchange rate against Rupiah and negatively affected by the value of the RCA index.